(untitled) (Annals of Medical Research, 2021)
Aim: There is a growing body of evidence suggesting that the concentration of presepsin in serum was found to be increased in patients with sepsis compared to healthy individuals, but the clinical significance of presepsin in the diagnosis of complicated acute appendicitis remains unclear. The purpose of this study was investigation of the diagnostic value of presepsin in complicated acute appendicitis. Material and Methods: This clinical prospective single-center study was conducted between May and August 2018, and comprised 120 patients with definitive diagnosis of acute appendicitis and 30 individuals as control group. White blood cell count (WBC), C-reactive protein (CRP), neutrophil/lymphocyte ratio (NLR) and presepsin levels were measured from venous blood samples. A receiver operating characteristic (ROC) curve was constructed to assess sensitivity and specificity as well as optimal cut points for each presepsin to diagnose acute appendicitis.Results: Serum levels of CRP, WBC, NLR and presepsin were higher in complicated group compared with uncomplicated (p0.0001, p=0.01, p=0.034 and p0.0001, respectively). The time of hospitalization, the rate of postoperative infection, intraabdominal abscess and re-hospitalization were significantly higher in complicated group (p0.0001, p=0.0009, p=0.0073 and p=0.0073, respectively). Comparing the diagnostic test results with ROC analysis, variable WBC (AUC=0.646, p=0.0052), CRP (AUC=0.807, p0.001), NLR (AUC=0.620, p=0.0305) and presepsin (AUC=0.965, p0.001) were significant parameters in predicting the presence of complicated acute appendicitis. Cut-off points of CRP, WBC, NLR and presepsin were calculated as 13.5 mg/dL, 1.4 x103/uL, 4.79 and 272 pg/ml. AUC of presepsin was larger than AUCs of WBC, CRP and NLR, suggesting the highest predicting power of presepsin among other parameters.Conclusion: Plasma presepsin level with CRP, WBC and NLR are valuable diagnostic parameters to predict complicated acute appendicitis.